2004
DOI: 10.1111/j.1525-1594.2004.07348.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of Dynamic Characteristics of the VentrAssist Implantable Rotary Blood Pump

Abstract: The VentrAssist implantable rotary blood pump, intended for long-term ventricular assist, is under development and is currently being tested for its rotor-dynamic stability. The pump consists of a shaftless impeller, which also acts as the rotor of the brushless DC motor. The impeller remains passively suspended in the pump cavity by hydrodynamic forces, which result from the small clearances between the outside surfaces of the impeller and the pump cavity. These small clearances range from approximately 50 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The damping effect of the impeller in water increased due to the rotation. However, it is not clear from this data whether the damping effect is due to the additional mass effect or the increase of both the damping coefficient and the spring stiffness produced by the hydrodynamic effect (18). A detailed analysis of the dynamic characteristics of the impeller in the axial Z direction should be carried out in future work.…”
Section: Stiffness and Dampingmentioning
confidence: 93%
“…The damping effect of the impeller in water increased due to the rotation. However, it is not clear from this data whether the damping effect is due to the additional mass effect or the increase of both the damping coefficient and the spring stiffness produced by the hydrodynamic effect (18). A detailed analysis of the dynamic characteristics of the impeller in the axial Z direction should be carried out in future work.…”
Section: Stiffness and Dampingmentioning
confidence: 93%
“…Michael K.H. Chung et al (40) of the University of Technology (Sydney, Australia) evaluated the dynamic characteristics of their impeller‐bearing‐pump housing of their rotary blood pump for increasing pump speeds. The results indicated that stiffness and damping coefficients increased as flow rate and pump speed increased representing an increase in stability with these changing conditions.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%
“…Therefore the risk to fall into sever suction can be reduced and also inlet pressure can be kept in physiological level. Highly sophisticated blood pumps for LVAD are centrifugal flow pump or axial flow pump [7][8][9]. Especially centrifugal pumps can obtain passively-created pulsatile flow which is induced by native heart beat.…”
Section: Introductionmentioning
confidence: 99%